2017
DOI: 10.3329/akmmcj.v6i2.31588
|View full text |Cite
|
Sign up to set email alerts
|

Depression Among Rural Aged : Facts & Reasons

Abstract: general population and approximately 10% in chronically ill medical out patients. It is a major cause of disability and of suicide. If comorbid with a medical condition depression magnifies disability, diminishes adherence to medical treatment and rehabilitation and may even shorten life expectancy. Such comorbid depression may incrementally worsen health more than any combination of chronic diseases without depression 2 .There is ongoing debate as to whether the prevalence IntroductionDepression is a common p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…In the past studies, another cut-off point [4/5] was used for the same screening instrument . The most noticeable finding is that the prevalence of geriatric depression in our study is considerably higher than what has been found in population-based studies from various other Asian countries; 45% in Bangladesh [30] [40], and 17.2% in Vietnam [33]. It is noteworthy that depression among adults (18-65 years) in a recently conducted nationwide study population in Nepal was also found to be higher than the global mean [41].…”
Section: Discussioncontrasting
confidence: 74%
“…In the past studies, another cut-off point [4/5] was used for the same screening instrument . The most noticeable finding is that the prevalence of geriatric depression in our study is considerably higher than what has been found in population-based studies from various other Asian countries; 45% in Bangladesh [30] [40], and 17.2% in Vietnam [33]. It is noteworthy that depression among adults (18-65 years) in a recently conducted nationwide study population in Nepal was also found to be higher than the global mean [41].…”
Section: Discussioncontrasting
confidence: 74%
“…In the past studies, another cut-off point [4/5] was used for the same screening instrument [GDS-15]. The most noticeable finding is that the prevalence of geriatric depression in our study is considerably higher than what has been found in population-based studies from various other Asian countries; 45% in Bangladesh [30]; 30.8% in China [31], 33.8% in Indonesia [32], 33.3% in Japan [33], 39.7% in Korea [34], 48.3% in Laos [35], 22.9% in Myanmar [36], 40.6% in Pakistan [29], 27.8% in Sri Lanka [37], 22.2% in Singapore [38], 27.5% in Taiwan [39], 27.5% in Thailand [40], and 17.2% in Vietnam [33]. It is noteworthy that depression among adults (18–65 years) in a recently conducted nationwide study population in Nepal was also found to be higher than the global mean [41].…”
Section: Discussionmentioning
confidence: 49%
“…25 Among elderly population, prevalence of mild and moderate depression was found to be 27% and 18% respectively and was also associated with several health ailments. 26 The high prevalence and disability associated with depression, poor awareness and care seeking and low detection rates by health care professionals makes a case to find alternative ways to identify people with depression for appropriate management. Self-rated health (SRH) is a one-item simple question that has been used in several studies for population health monitoring.…”
Section: Introductionmentioning
confidence: 99%